2010
DOI: 10.4315/0362-028x-73.8.1447
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Food Safety Management Systems in Poultry Meat Preparation Processing Plants in Relation to spp. Contamination

Abstract: A diagnostic instrument comprising a combined assessment of core control and assurance activities and a microbial assessment instrument were used to measure the performance of current food safety management systems (FSMSs) of two poultry meat preparation companies. The high risk status of the company's contextual factors, i.e., starting from raw materials (poultry carcasses) with possible high numbers and prevalence of pathogens such as Campylobacter spp., requires advanced core control and assurance activitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(27 citation statements)
references
References 28 publications
1
23
0
3
Order By: Relevance
“…The findings concur with previous studies which indicated that poor hygiene was evidenced by the presence of E. coli (Ghafir et al, 2008;Jacxsens et al, 2009;Sampers et al, 2010). The presence of E. coli violates regulations which prohibit the presence of pathogenic and spoilage microorganisms in any food item intended for human consumption (Dairy Regulations, 1977;Food and Food Standards Act, 2001;Public Health Act, 2001;CAC, 2003).…”
Section: Discussionsupporting
confidence: 90%
“…The findings concur with previous studies which indicated that poor hygiene was evidenced by the presence of E. coli (Ghafir et al, 2008;Jacxsens et al, 2009;Sampers et al, 2010). The presence of E. coli violates regulations which prohibit the presence of pathogenic and spoilage microorganisms in any food item intended for human consumption (Dairy Regulations, 1977;Food and Food Standards Act, 2001;Public Health Act, 2001;CAC, 2003).…”
Section: Discussionsupporting
confidence: 90%
“…The actual microbiological assessment found variable and high counts of TVC in raw materials, final products and food contact surfaces as well as Enterobacteriaceae in food contact surfaces. (Sampers et al, 2010), f (East African Community, 2010b); **Same as product handled in the respective area. i lowest and highest CFU counted in all three visits within a specific CSL; NA -not applicable; ** The results are expressed in log CFU/50 cm 2 for products and log CFU/25 cm 2 for contact surfaces (filtration tray, filling machine) and hands of personnel.…”
Section: Discussionmentioning
confidence: 99%
“…Uncertainty can be reduced by adequate information and systematic methods; ambiguity, by scientific information; and vulnerability, by systematic methods and independent positions . More advanced control and assurance activities are described as being based on scientific input, using companyspecific information, structured analysis, procedure driven, and independent assurance (Luning et al, 2008Sampers et al, 2010).…”
Section: Framework Of Fsms-dimentioning
confidence: 99%